L'ecografia del rene trapiantato: caratteristiche specifiche e utilizzo nella pratica clinica - Carlo Maria Alfieri; Marianna Tangredi; Silvia Giuliani; Piergiorgio Messa (AboutScience Srl, 2020)
Renal transplantation (RTx) is at the moment the best therapy for end stage renal disease. In recent years, the increase of the global knowledge about immunology and RTx complications allowed a significant increase in the duration of RTx and in patients' survival. RTx ultrasound gives to transplant clinicians the possibility of carrying out a structural monitoring of the graft from the beginning throughout the duration of the RTx. Then, ultrasound is a first-level method that all clinicians should be able to perform and interpret. In this paper we will present some basic concepts about the ultrasound image of the "healthy" transplanted kidney, relating them to the main pathological pictures that may occur during a clinical-ultrasound monitoring of the RTx. Finally, some concepts regarding the use and usefulness of ultrasound with contrast media (CEUS) in the evaluation and the follow-up of RTx will be discussed.